Duration Effects of Shrimp Paste Storage on ALT of Mold Colonies: Variations by Brand and Pre-Standard Treatment - Syafitri, Nur Laila; Hastuti, Utami Sri; Prabaningtyas, Sitoresmi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Shrimp paste is a commonly employed condiment or flavoring in culinary preparations. As a result of the nutrients present in shrimp paste, fungi and other microbial contaminants are able to proliferate and develop on the paste. This study aims as follows: 1) to determine ALT measurements of mold colonies to assess the quality of two brands of pre-treated shrimp paste; and 2) to identify contaminating mold species present in steamed and unsteamed shrimp paste prior to storage. Descriptive quantitative and qualitative research methods were employed within the Biology Department of FMIPA UM's Microbiology Laboratory. A series of three samplings were conducted on treated shrimp paste brands A and B, one week apart between each sampling. A volume of 90 ml of 0.1% peptone water was used to dissolve 10 grams of shrimp paste, resulting in a dilution of 10-1; this process was repeated until the dilution reached 10-5. 0. The surface of PDA (Potato Dextrose Agar) medium was inoculated with 1 ml of suspension from each dilution. The medium was subsequently incubated at a temperature of 25oC for 7x24 hours. The findings of this study indicate the following: 1) At the 28th day of storage, both brands of shrimp paste that underwent treatment with steamed and unsteamed shrimp paste remained of acceptable quality for human consumption. 2) In steamed and unsteamed shrimp paste, thirteen species of mold contaminants were identified: Chrysosporium corda, Cladosporium sphaerospermum, Penicillium frequentans, Penicillium chrysogenum, Rhizoctonia sp1., Aspergillus candidus, Fusarium equeseti, Colletotrichum ti, Moniliella acetobutens, and Rhizoctonia sp3